Looking for a moose - Root, Phyllis; Cecil, Randy (Cambridge, Mass. : Candlewick Press, 2006)
Four children set off into the woods to find a moose.
Adult 480
Accelerated Reader AR
Keywords: Moose -- Juvenile fiction; Stories in rhyme